Giacomo Verde installazioni, tv interattive, net art, tecnoteatro (1992-2002) - Monteverdi, Anna Maria (Milano University Press, 2023)
Giacomo Verde (Cimitile 1956-Lucca 2020), video artist and techno performer, has dedicated his entire life to the creation of a social and participatory art that directly engages the audience in the creative process, with the use of analogue, digital and web technologies. Verde was a tireless experimenter with new technologies, favouring the use of a poor technology, reinvented in relation to changing expressive needs. The present book follows, just over a year later, the previous text entitled Giacomo Verde. Attraversamenti tra teatro e video (1986-1992), also published by Milano University Press. The research is continued in this volume, which aims to show the artist's work in the period 1993-2003 through preparatory materials for interactive performances and installations that highlight the importance of drawing as a substantial medium in Verde's technological creative process.